Carbazole/triazine based host materials for high-performance green PhOLEDs. (March 2022) - Qu, Wenshan; Gao, Zhixiang; Li, Wei; Fan, Xiaxia; Shi, Yunlong; Miao, Yanqin; Wu, Zhongxin; Huang, Jinhai; Wang, Hua; Wei, Bin
Abstract: In this work, two novel compounds, namely TCz1DF and TCz4DF, were reported as the host materials for green organic light emitting devices. These two bipolar materials are constructed from hole transport group carbazole and electron transport group triazine, which have high thermal stability, suitable energy levels and good charge transfer abilities. The green phosphorescent OLEDs based on these two materials exhibit quite good performance. The maximum external quantum efficiency (EQE) of device G1 based on TCz1DF can be achieved 16.5%, and the EQE of device based on TCz4DF can also reach 15.4%. At the same time, the efficiency roll-off of these devices is very insignificant. Under 1000 cd m −2 brightness, the EQEs of devices G1 and G2 can reach 16.4% and 15.2%, which are almost equal to their maximum values. Highlights: Two novel host materials were reported for green phosphorescent OLEDs. These two materials possess balanced charge transport abilities. Green light-emitting devices based on these two host materials exhibit high efficiency.